Self-medication practices in Ethiopia: An umbrella review protocol. - Getahun Fetensa; Eshetu Ejeta; Tariku Tesfaye Bekuma; Feyiso Bati; Edosa Amante; Jaleta Bulti; Saro Abdella; Yosef Gebreyohannes; Sabit Ababor; Abera Botore; Dabesa Gobena; Mirkuzie Woldie; et al. (PLoS ONE)
Background Self-medication is the practice of obtaining and using drugs without proper guidance or supervision. It can involve various behaviours that may harm individuals and society. Self-medication can cause serious health and economic problems for countries and healthcare systems. Therefore, current review aimed at examining self-medication practices in Ethiopia. Methods This umbrella review will consider all systematic reviews that include self-medication practices of adult age greater than 18 years in Ethiopia. Study protocols, papers other than systematic reviews, papers not reporting on self-medication practices, and papers published in languages other than English will be excluded from the review. MEDLINE, Embase, and the Cochrane Database of Systematic Reviews will be searched. Two reviewers will screen the titles and abstracts against the eligibility criteria. Data extraction will be performed by 2 independent reviewers on the reviews selected for inclusion. The characteristics of studies like author name, year published, databases searched, number of studies/patients included, and self-medication practices will be extracted. The quality of included studies will be reported using the JBI critical appraisal checklist for systematic reviews and research syntheses. A summary of the extracted data will be presented in tabular format and a narrative synthesis will be performed on the collected systematic reviews that meet the inclusion criteria. Discussion This protocol is expected to bring pooled evidence on self-medication practice among different population groups like pregnant mothers, adult population, students, and general population. Evidence from this review will be used to tackle current global problem related with anti-microbial resistance. Therefore, our review will call for government and non-government interventions in reducing current challenge of global issue related with anti-microbial resistance in resource limited country like Ethiopia. Systematic review registration number PROSPERO CRD42023182552.